The Ability of Edible Fungi Residue to Remove Lead in Wastewater - Jing, Yanyan; Li, Zongyu; Li, Yameng; Lei, Gao; Li, Liangliang; Yang, Xin; Zhang, Zhilong; Yang, Wenling (Frontiers in Environmental Science, 2021)
Lead (Pb)-contaminated wastewater is the most common source of heavy metal ion pollution. In this study, agricultural waste edible fungi residue (EFR) was used to adsorb Pb(II) ions in wastewater as a strategy to reduce environmental pollution and minimize poisoning by Pb. The influence of Pb(II) concentration, solution pH, and EFR concentration on the removal efficiency (R) of Pb(II) was investigated with single factor design and response surface analysis. The maximum predicted R for Pb(II) was 76.34% under optimal conditions of Pb(II) concentration of 483.83 mg/L, EFR concentration of 4.99 g/L, and pH of 5.89. The actual experimental value of R reached 76.97% under these conditions. The competition of Pb(II) ions for the available adsorption sites on EFR limited the maximum R. A comparison of Fourier transform infrared spectroscopy before and after the adsorption of Pb(II), indicated that the functional groups of EFR significantly affected the effect of adsorption of heavy metals, and that the adsorption process was primarily affected by functional groups in the range of wavenumbers from 500 to 2000 cm-1.